Insights into Genotype × environment interactions affecting essential oil yield and quality stability in Cymbopogon species and genotypes - Lal, R.K.; Chanotiya, C.S.; Lahiri, Rashami (Biochemical systematics and ecology, 2025)
To explore the stability and chemical composition of essential oil yield in diverse Cymbopogon genotypes, a genotype × environment interaction (GEI) study was conducted using germplasm from the CSIR-CIMAP Lucknow National Gene Bank. Essential oil profiles varied across species: lemongrass (C. citratus) predominantly contained citral (geranial and neral), while Java citronella (C. winterianus) was rich in citronellal, citronellol, and geraniol. Chemotypes such as methyl eugenol, geranyl acetate, and myrcene were also detected. Pooled ANOVA revealed significant effects of genotype (G), environment, and GEI for all traits except X7. IPCA1 was significant for every attribute, indicating the relevance of GEI in trait expression. Correlation analysis showed positive associations between oil content and compounds such as limonene, citronellal, geraniol, and geranyl acetate, while geranial and neral were negatively correlated with essential oil yield. Notably, neral and geranial were positively correlated with each other. For herbage yield, genotypes GEN 12, 1, 7, and 6 performed best; for essential oil content, GEN 12, 1, 7, and 13 were superior. Stability analysis across environments identified GEN 12 and 1 as the most consistent yield traits. GEN 5, 11, 14, and 8 were stable for neral content, and GEN 9, 15, 4, and 5 for geranial. These findings highlight the genetic diversity and stability of select Cymbopogon genotypes, supporting their use in breeding programs and recommending them for pilot-scale cultivation and varietal release aimed at enhanced and stable essential oil production. [Display omitted] •Essential oils of Cymbopogon species are highly valued in perfumery, pharmaceutical industries.•Citral is also used in the production of vitamin A and ionones.•Neral and geranial had positive correlations, neral was negatively associated with citronellal.•For herb yield, genotypes GEN 12, 1, 7, 6; for the essential oil %, GEN 12, 1,7 13 were superior.